2015
DOI: 10.1155/2015/320780
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Emergency: Testicular Torsion in the Inguinal Canal

Abstract: Objectives. To report our experience and present the largest series of testicular torsion cases in the inguinal canal. Material and Methods. The clinical data of 13 patients with testicular torsion in the inguinal canal treated between 2005 and 2013 were reviewed. Recorded patient age, whether the testes were palpable or not, side of the affected testes, the presence of hernia, ischemia time, and operation outcomes were assessed. Results. Patient age ranged from 8 to 70 months (29.15 ± 20.22). Mean ischemia ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 21 publications
0
16
1
Order By: Relevance
“…Pogorelić et al [4] reported that 3 out of 8 cases of cryptorchidism were rescued and they were all over 13 years of age, and within 6 h from the onset of symptoms. Şener et al [7] reported that the rescue rate was about 90% within 6 h from the onset of symptoms and decreased to less than 10% 24 h after the onset of symptoms. In addition to the duration of testicular torsion, the degree of torsion and outcome are also closely related.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pogorelić et al [4] reported that 3 out of 8 cases of cryptorchidism were rescued and they were all over 13 years of age, and within 6 h from the onset of symptoms. Şener et al [7] reported that the rescue rate was about 90% within 6 h from the onset of symptoms and decreased to less than 10% 24 h after the onset of symptoms. In addition to the duration of testicular torsion, the degree of torsion and outcome are also closely related.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical manifestations of the torsion of an UDT often lack specific symptoms and signs, and include irritability, nausea and vomiting, atypical abdominal pain and groin area pain [4,7]. Most of the abdominal type of UDT shows only mild tenderness in the abdomen, often without peritoneal irritation, and may be easily misdiagnosed as appendicitis [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sener et al . ( 12 ), the oldest patient was only 5 years and 10 months old ( p = 0.0562), with shorter range of participants' age. Both studies showed a statistically significant difference compared to our series of patients.…”
Section: Resultsmentioning
confidence: 94%
“…Although the incidence of torsion is higher in cryptorchid testis, there are only isolated reports of torsion of undescended testicle. [ 4 ]…”
Section: Discussionmentioning
confidence: 99%